EFL Teachers’ Perception and Strategies for Integrating Character Education into the Lesson - Putri, Ni Putu Julia Eka; Artini, Luh Putu; Wahyuni, Luh Gede Eka (Jurnal Pendidikan dan Pengajaran, 2020)
The recent phenomena of moral degradation of Indonesian youth are responded by policy in moral and character education. Character education in schools is included in the curriculum and it must be integrated into the subjects matter. This study aims at investigating how English teachers perceive character education in the context of teaching English as well as the strategies in inserting character education into the lesson by conducting explanatory sequential mixed method design. The participants of this study were seventh and eighth grade English teachers in SMPN 6 Singaraja. The data were collected by means of questionnaire, observation sheet, and interview guide. As the result, this study revealed that English teachers had sufficient knowledge of Character Education concept. The way they implemented the character education did not really represent how character education should be inserted. Furthermore, they also were not sure of its impact to the students’ character development. It indicates that they had lack understanding of character education and the implementation of character education. The way English teachers integrate character education into further learning is discussed in a research discussion. Furthermore, enriching their knowledge of the character education should be the first step done.